RHOMBENCEPHALITIS POSSIBLY CAUSED BY MYCOPLASMA PNEUMONIAE - Aamir Khan,; Ayaz Ul Haq,; Hira Hamid,; Tanvir Fatima,; Shakira Adnan, (Journal of Ayub Medical College Abbottabad, 2022)
We report a rare case of encephalitis that is not often described in clinical settings in neurology. Our case was 11-year-old female patient who had presented with features of meningoencephalitis, but not responded to the conventional treatment. Her magnetic resonance imaging revealed lesions in thalami, cerebellum and brainstem. The differentials in this age were infective and inflammatory causes of meningoencephalitis and acute disseminated encephalomyelitis (ADEM). Paraneoplastic was another differential. Mycoplasma serology came out positive. As a result, diagnosis of mycoplasma pneumoiae associated Rhombencephalitis was made based on diagnosis of exclusion.